INFUENCE OF COMPLEX PROGRAM OF METABOLISM OPTIMIZATION ON WORKING CAPACITY OF ATHLETES - K. A. Karuzin; V. I. Boitsov; A. K. Martusevich; S. P. Levuschkin (Кубанский научный медицинский вестник, 2016)
The aim of this paper is estimation aerobic and anaerobic working capacity of sportsmen under use of the complex program of metabolism optimization. Athletes of the main group (n=24) were tested on metabolism state with paid attention to antioxidant potential. These data were used for selection of individual complex of vitamins and antioxidants. In main group study of working capacity, including technologies of its estimation (veloergometry, gas analysis, investigation of maximal anaerobic power etc.) was executed before and after the course of this complex use. In control group (n=30) indicated testing was providing analogically. Our results have shown the positive action of directed optimization of the metabolism on parameters of aerobic and anaerobic physical capacity of sportsmen.